Effect of Phosphorus Solubilizing Bacteria on Nutrients uptake by Broad bean (Vicia faba L.) Plant and phosphorus availability at different Phosphorus Levels - Mohammed, Sarkawt Zorab; Fattah, Omar Ali (Sulaimani Journal for Pure and Applied Sciences, 2018)
This research was conducted at the plastic house at the College of Agricultural Sciences, University of Sulaimani, Bakrajo, during 2016 to study the effect of phosphorus solubilizing bacteria (Bacillus megaterium) at different phosphorus levels (0, 40, 80, 160 and 320) kg P ha-1 in calcareous soil on uptake of some nutrients in broad bean plants and phosphorus availability. The experiment was performed in a factorial experiment with completed randomized design (CRD) in a silty clay loam soil, with three replications for each treatments, thus the total number of experimental units was (2×5×3=30) units. After ten weeks of growth, the plants were harvested to determine plant shoot nutrients content of (N, P, k, Fe and Zn and available phosphorus in soil. The following results were obtained inoculating soil with phosphorus solubilizing bacteria was significant for increasing shoot N, P, K, and Fe content, the highest values were 11.61 g kg-1, 3.82 g kg-1, 16.18 g kg-1 and 90.66 µg g-1 respectively, recorded at highest P level (320 kg P ha-1), while the highest value for shoot Zn content was 52.83 µg g-1 recorded at medium P level (80 kg P ha-1) and the highest value for available P in soil was 10.36 µg l-1 recorded at highest P level (320 kg P ha-1).
Keywords: Phosphorus Solubilizing Bacteria; Rock Phosphate; Broad bean